Characterisation of nano-assemblies inside mesopores using neutron scattering*. (18th August 2021) - Ma, Yingzhen; Heller, William T.; He, Lilin; Shelton, William A.; Rother, Gernot; Bharti, Bhuvnesh
Abstract : Adsorption of molecular and nanoscale matter in mesoporous materials is important in filtration and chromatography as well as membrane processes. However, the morphology and distribution of self-assembled structures of adsorbate formed within nanoconfined environments is largely unknown. Small Angle Neutron Scattering (SANS) with porous matrix matching the neutron scattering length density of the solvent has the potential to provide detailed information on the self-assemblies formed in pore spaces. However, analysis of such SANS profiles remains a challenge. In this study, we extend the SANS analysis method previously developed by Findenegg and co-workers to include interparticle correlations, providing a qualitative characterisation of the adsorption state of surfactants and nanoparticles in the cylindrical pores of silica nanomaterials. We find that the pore filling fraction and the self-assembled state of the adsorbate governs the scattering profile. We apply the model to two materials namely, triethyleneglycol monohexyl ether (C6 E3 ) surfactant and gold nanoparticles adsorbed in SBA-15 mesoporous silica. In contrast to the C6 E3 system, Bragg scattering dominates the diffuse scattering in gold nanoparticle system, which we attribute to the immobile internal structure of the nanoparticles. This new SANS analysis method has potential to elucidate structures of soft matter nanoassemblies inside mesopores. GRAPHICAL ABSTRACT: UF0001